METABOLIC ENGINEERING OF MICROORGANISM FOR THE PRODUCTION OF CARBOXYLIC ACID AND THEIR INHIBITORY EFFECTS. - SARFRAZ, HIRA; ALI, SIKANDER; MUSHTAQ, JAVERIA; NAZIR, FARZANA (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
To fulfill the requirement of futurre coming perspective for chemicals like carboxylic acid that are produced by microbial fermentation are an excellent biorenewable chemical. Due to their demand and usage as precursor for a number of industrial chemical, it can be produced through engineered microbes such as Saccharomyces cerevisiae, E.coli and Bascilus subtilis. Genetic engineering is now successfully and commonly used to change carbon to ethanol the end product of Saccharomyces cerevisiae to pyruvate. Genetic manipulation methods are useful for pathway design and for the production of several organic acids. Deletions of metabolic pathways that compete with the target compound are produces, can be a useful method for redirecting metabolic flux into the desired pathways. However carboxylic acids become increasingly inhibiting to the microorganisms. These inhibitors at their specific potency are commonly used as food preservative. The effects of carboxylic acids include cell membrane damage, change in microbial internal pH. Certain changes in cell membrane properties such as fluidity, composition, integrity and intracellular pH and hydrophobicity are associated with increase tolerance. These desirable products can use in the engineering of robust strains with improved industrial performance.